GAMBARAN FOTO TORAKS PASIEN PENYAKIT PARU YANG MENGALAMI HEMOPTISIS PERIODE FEBRUARI - JUNI 2018 DI RSUD DR. PIRNGADI MEDAN - RIZKY NURDIANTY; IKHFANA SYAFINA; DEDY DWI PUTRA; DES SURYANI (JURNAL ILMIAH SIMANTEK, 2021)
Hemoptysis is a symptom of removal of blood from mouths that are filled with a feeling of wanting to cough hematemesis ablood drain, black which is not and weal. To find out the picture of the chest X ray of patients with pulmonary disease whoexperienced symptoms of hemotysis in February 2018 – june 2018 at Dr. Pirngadi Medan. The type to be used in thisresearch is descriptive research and cross sectional research design. study. Population is patient of polyclinic of lung atRSUD Dr. Pirngadi Medan. The sample in this study is the medical record data from febuary 2018 – june 2018 in patients inthe pulmonary clinic RSUD Dr. Pirngadi Medan. The results of chest X-ray images in lung patients with most hemoptysissymptoms were infiltrates of 40 (75.5), the most gender who experience symptoms of hemoptysis are men as many as 40(75.5%), the highest age who experience symptoms of hemoptysis is 21-30 years as many as 22 (41.5%), the most lungdiagnosis of hemoptysis is 30 pulmonary tuberculosis (56.6%). There is a picture of chest X-ray infiltrates more common inlung disease patients with hemoptysis symptoms.